Magnetic and transport properties of La₀.₈Sr₀.₂MnO₃/La₀.₈Ca₀.₂MnO₃ bilayer - Prokhorov, V.G.; Kaminsky, G.G.; Komashko, V.A.; Lee, J.S.; Park, Y.P. (Физика низких температур, 2003)
The effects of lattice strain on the magnetic and the transport properties of La₀.₈Sr₀.₂MnO₃ films grown on an (001) LaAlO₃ substrate and on a La₀.₈Ca₀.₂MnO₃ layer were studied. It was observed that the metal-insulator and the ferromagnetic transitions occur at higher temperatures for the film deposited on La₀.₈Ca₀.₂MnO₃ layer than on LaAlO₃. The dependence of Curie temperature on the bulk and the Jahn-Teller strains were also determined.